Handbook of plant food phytochemicals : sources, stability and extraction - Tiwari, Brijesh K.; Brunton, Nigel; Brennan, Charles S. (Wiley-Blackwell, 2013)
Phytochemicals are plant derived chemicals which may bestow health benefits when consumed, whether medicinally or as part of a balanced diet. Given that plant foods are a major component of most diets worldwide, it is unsurprising that these foods represent the greatest source of phytochemicals for most people. Yet it is only relatively recently that due recognition has been given to the importance of phytochemicals in maintaining our health. New evidence for the role of specific plant food phytochemicals in protecting against the onset of diseases such as cancers and heart disease is conti.